1995
DOI: 10.1161/01.cir.92.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen After Coronary Angioplasty as a Risk Factor for Restenosis

Abstract: An independent relation exists between von Willebrand factor measured immediately after angioplasty and restenosis defined by the degree of intraluminal renarrowing. An elevated fibrinogen level during follow-up is a strong biochemical predictor of restenosis. Therefore, fibrinogen should be considered at least as an independent marker of restenosis and perhaps as a common risk factor for both spontaneous coronary atherosclerosis and postangioplasty restenosis, which is an accelerated form of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(48 citation statements)
references
References 38 publications
3
43
1
1
Order By: Relevance
“…1,4,5,13,16,17) The results of this study extend our previous observations, demonstrating the predictive value of measuring plasma levels of IL-8 for early complications after coronary interventions. Buffon, et al reported that the preprocedural CRP level is a powerful predictor of both early and late outcome in patients undergoing single vessel PTCA.…”
Section: Discussionsupporting
confidence: 86%
“…1,4,5,13,16,17) The results of this study extend our previous observations, demonstrating the predictive value of measuring plasma levels of IL-8 for early complications after coronary interventions. Buffon, et al reported that the preprocedural CRP level is a powerful predictor of both early and late outcome in patients undergoing single vessel PTCA.…”
Section: Discussionsupporting
confidence: 86%
“…High vWF levels have been associated with CAD (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In the present study patients showed higher plasma vWF levels than controls, but this difference was not significant.…”
Section: Discussioncontrasting
confidence: 65%
“…High levels of vWF have been associated with cardiovascular disorders such as ischemic heart disease, peripheral and pulmonary vascular disease, cerebrovascular disease, left ventricular aneurysm, atrial fibrillation, and deep venous thrombosis, as reviewed by Lip and Blann (1). Some studies have shown that high plasma vWF levels are a significant and independent predictor of cardiovascular risk in subjects with coronary artery disease (CAD) (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), but few studies have exam-D. Simon et al ined the relationships between vWF genotypes and coronary heart disease (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies conducted by Montalescot et al (1995) demonstrated that patients with restenosis showed elevations in several procoagulant factors such as PAI-1, tissue plasminogen activator antigen, fibrinogen, and factors VII and VIII. In addition, Ishiwata et al (1997) identified depression of the fibrinolytic response in patients who developed restenosis post-PCI as compared to those patients who did not develop restenosis.…”
Section: Oxidative Stress and Restenosismentioning
confidence: 92%